THE EFFECTIVENESS OF CORPORATE ADMINISTRATIVE SANCTIONS IN ENVIRONMENTAL LAW ENFORCEMENT IN MEDAN - Dedy Armaya; Isnaini; Maswandi (Universitas Negeri Medan, 2026)
This study analyzes the effectiveness of the application of administrative sanctions for corporations in environmental law enforcement at the Medan City Environmental Agency (DLH). The background of the research is the importance of administrative sanctions as a fast preventive and corrective instrument compared to criminal or civil channels. The method used is normative-empirical legal research with a normative juridical approach, supported by in-depth interviews and document studies. The results of the study show that normatively, the regulation of administrative sanctions in Law No. 32/2009 jo. Law No. 6/2023, Government Regulation No. 22/2021, and the Minister of Environment and Forestry Regulation No. 14/2024 is adequate and places corporations as subjects of environmental law. Empirically, the implementation of sanctions by the Medan City DLH shows relative effectiveness, reflected in the increase in corporate compliance with written warnings and government coercion, as well as changes in environmental management behavior. However, effectiveness has not been optimal due to obstacles such as the limited number of environmental supervisors, low legal awareness of business actors, weak coordination between agencies, and socio-economic dilemmas in imposing heavy sanctions (freezing/revocation of permits). It is necessary to strengthen institutional capacity, increase supervision, and foster sustainable compliance to realize more effective environmental law enforcement. Keywords: Administrative Sanctions, Corporation, Environmental Law.